2011
DOI: 10.1002/ejoc.201101206
|View full text |Cite
|
Sign up to set email alerts
|

Green Catalysts Derived from Agricultural and Industrial Waste Products: The Preparation of Phenols from CsOH and Aryl Iodides using CuO on Mesoporous Silica

Abstract: The synthesis of CuO catalysts supported on mesoporous silica derived from rice husks and semiconductor copper from chemical mechanical planarization (Cu-CMP) wastewater is described. These catalysts are active for the coupling reaction of CsOH with aryl iodides. Low catalyst loading (1 mol-%) without the need for ancillary ligands make these very attractive green catalysts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 34 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Lee, Lin, and co-workers described the synthesis of CuO on mesoporous silica catalyst and its application for hydroxylation . The characterization of the catalyst showed that CuO is well-dispersed into the surface of mesoporous silica, where the silicate support prevents the formation of CuO nanoparticles by agglomeration.…”
Section: Hydroxylationmentioning
confidence: 99%
“…Lee, Lin, and co-workers described the synthesis of CuO on mesoporous silica catalyst and its application for hydroxylation . The characterization of the catalyst showed that CuO is well-dispersed into the surface of mesoporous silica, where the silicate support prevents the formation of CuO nanoparticles by agglomeration.…”
Section: Hydroxylationmentioning
confidence: 99%
“…Thanks to the excellent work of Buchwald, , Beller, , You, Ma, and other groups, , remarkable progress has been made for the Pd- and Cu-catalyzed hydroxylation of aryl halide. However, the synthetic application of the Pd-catalyzed hydroxylation of aryl halide was limited, particularly for large-scale preparation due to the high cost of Pd catalysts and phosphine ligands. Consequently, the development of the Cu-catalyzed hydroxylation attracted plenty of attention, and it had been demonstrated that a variety of bidentate ligands could successfully promote the transformation in recent years. , Ma and co-workers, especially, recently developed a CuI-mediated hydroxylation of (hetero)­aryl halides under mild conditions promoted by a bis-oxalamide ligand and realized the direct hydroxylation of aryl chlorides . In addition, 2-hydroxylcarbazoles could be prepared through an intermolecular ring closure via the nitrene intermediate, Pd­(II)-catalyzed C–H bond activation, or Pummerer reaction of sulfinyl compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Water hyacinth pre-treated with alkali and enzyme showed the maximum endoglucanase activity of 11.42U/ml, while sawdust showed the lowest reduced sugar yield (1.12 mg/ml) when treated with enzyme, and the lowest saccharification rate (5.92%) when treated with alkaline. Chan (2011) showed that rice husks can be used as a catalyst in the preparation of phenols from CsOH and aryl iodides using CuO on mesoporous silica.…”
Section: Biofertilizers Cultivation Materials and Soilmentioning
confidence: 99%